If we have integers $x,y,z$ such that $x,y,z \ge 3,$ find all solutions to $$\frac{1}{x} + \frac{1}{y} - \frac{1}{z} = \frac12.$$

I was thinking of first expanding out this, and then simplifying from there, but the equation got very messy. Is there a better method?


WLOG let $x\leq y$. Then, we have that $x = 3$ because we are given that $x\geq 3$, and if $x\geq 4$, $\frac{1}{x}+\frac{1}{y}\leq \frac{1}{2}$.

Then, we must solve $\frac{1}{y}-\frac{1}{z} = \frac{1}{6}$. Note that $y = 3,4,5$ because they are the only values such that $y\geq 3$ and $\frac{1}{y}>\frac{1}{6}$. Then, we can go into casework:

For $y = 3$, we get $\frac{1}{z} = \frac{1}{6}$ and thus $z = 6$.

For $y = 4$, we get $\frac{1}{z} = \frac{1}{12}$ and thus $z = 12$.

Finally, for $y = 5$ we get $\frac{1}{z} =\frac{1}{30}$ and thus $z = 30$.

We must permute $x$ and $y$ when they are different to get all of the solutions because of the earlier WLOG.

Thus, the only solutions are $\boxed{(3,3,6),\ (3,4,12),\ (3,5,30),\ (4,3,12),\text{ and }(5,3,30).}$


As an alternative to Joshua Wang's excellent answer:

By symmetry we may assume, without loss of generality, that $x\leq y$. Clearing denominators yields $$2xz+2yz-2xy=xyz,\tag{1}$$ and a bit of rearranging then shows that $$xy(z+2)=2(x+y)z.$$ Of course $z+2>z$ and so $xy<2(x+y)$, or equivalently $$(x-2)(y-2)<4.$$ Because $x\leq y$ we see that $x<4$, so $x=3$ and then $y<6$. Plugging into $(1)$ and rearranging shows that $$yz+6y-6z=0,$$ or equivalently $z=\frac{6y}{6-y}$, yielding the following three solutions for $(x,y,z)$: $$(3,3,6),\qquad(3,4,12),\qquad(3,5,30).$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.